2020
DOI: 10.1002/hbm.25321
|View full text |Cite
|
Sign up to set email alerts
|

Machinelearning‐basedmultimodal prediction of language outcomes in chronic aphasia

Abstract: Recent studies have combined multiple neuroimaging modalities to gain further understanding of the neurobiological substrates of aphasia. Following this line of work, the current study uses machine learning approaches to predict aphasia severity and specific language measures based on a multimodal neuroimaging dataset. A total of 116 individuals with chronic left‐hemisphere stroke were included in the study. Neuroimaging data included task‐based functional magnetic resonance imaging (fMRI), diffusion‐based fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 92 publications
(161 reference statements)
0
25
0
Order By: Relevance
“…This is consistent with our observation that the small clusters of structural disconnection associated with deficits in semantic cognition largely followed lesioned substrates, although a different pattern was found for executive dysfunction. Hope et al (2018) similarly found limited predictive value of indirectly measured structural disconnection beyond lesion location for predicting aphasia severity, while other studies have suggested unique contributions from such measures (Del Gaizo et al, 2017; Kristinsson et al, 2021). It may be that structural disconnection is unlikely to explain unique variation in behavioural performance beyond lesion location when patients have been selected to show particular deficits associated with areas of cortex that are lesioned, as was the case for semantic deficits in our sample.…”
Section: Discussionmentioning
confidence: 94%
“…This is consistent with our observation that the small clusters of structural disconnection associated with deficits in semantic cognition largely followed lesioned substrates, although a different pattern was found for executive dysfunction. Hope et al (2018) similarly found limited predictive value of indirectly measured structural disconnection beyond lesion location for predicting aphasia severity, while other studies have suggested unique contributions from such measures (Del Gaizo et al, 2017; Kristinsson et al, 2021). It may be that structural disconnection is unlikely to explain unique variation in behavioural performance beyond lesion location when patients have been selected to show particular deficits associated with areas of cortex that are lesioned, as was the case for semantic deficits in our sample.…”
Section: Discussionmentioning
confidence: 94%
“…Recent literature has developed strategies to combine different data modalities (anatomical, functional, behavior, etc.) of stroke patients ( Iorga et al, 2021 , Kristinsson et al, 2021 , Pustina et al, 2017 ). While this study does not include anatomical information of the patients, future multimodal studies could adapt the presented methods to include the structural constraints of each individual subject.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a perfusion protocol is easier to administer, and can be more readily standardized across sites and hence included in routine clinical assessments. Perfusion measures, while previously largely overlooked in multimodal neuroimaging studies (with the notable exception of Kristinsson et al, 2021), may offer valuable prognostic indicators of recovery potential and should be routinely included in future studies investigating the neural mechanisms of post-stroke recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a perfusion protocol is easier to administer, and can be more readily standardized across sites and hence included in routine clinical assessments. Perfusion measures, while previously largely overlooked in multimodal neuroimaging studies (with the notable exception of Kristinsson et al, 2021)…”
Section: Discussionmentioning
confidence: 99%